Audit Komunikasi Program Intervensi Keamanan Pangan Jajanan Anak Sekolah Balai Besar Pengawas Obat dan Makanan di Yogyakarta - Wulandari, Wulandari; Suparno, Basuki Agus; Prayudi, Prayudi (Eruditio : Indonesia Journal of Food and Drug Safety, 2024)
Unsafe school children's snacks (PJAS) pose health risks and can cause various diseases. To address this, the PJAS Safety Intervention Program was introduced. The COVID-19 pandemic brought changes to the definition of PJAS and altered communication patterns in program delivery. This study evaluates the success of the program implemented by the Indonesian Food and Drug Authority Regional Office in Yogyakarta during the pandemic. It identifies factors inhibiting its effectiveness through a communication audit. The research used an evaluative qualitative method involving interviews with informants to assess planning and preparation and surveys with school community respondents to evaluate program communication. The study followed the General Guidelines for Communication Audits in Government Agencies. Results indicate that the program was effectively implemented and can be enhanced by improving communication dimensions. Key strategies include strengthening message delivery through direct engagement with policymakers, expanding media use by adding hardcopy materials, improving message clarity with comprehensive posters detailing program stages, and fostering public feedback through information sharing and participation mechanisms, particularly at junior and senior high school levels. Additionally, expanding promotional media can further optimize program outreach. The communication audit concluded that the PJAS Safety Intervention Program successfully met its objectives through effective management with minor, manageable obstacles. These findings suggest that the program can continue with improved communication strategies to enhance its impact.